Justification of the Design of the Two-shaft Mixer of Forages. (2016) - Kushnir, V.; Gavrilov, N.; Kim, S.
Abstract: Justification of the use of mixers in the processing of mixtures' feed is given in the article. Some designs of mixers are considered, research of some authors are noted. Existing shortcomings of the mixing process and designs of mixers are revealed. The sound design of a double-shaft mixer with a horizontal shaft and rectangular buildings are given in the article on the basis of a priori review. The experimental feed mixer is designed and manufactured on the basis of objectives and research hypotheses, a description which allows us to understand the essence of the work. In addition, the article reflects the theoretical calculation of the lobed mixer, the technique of the experiments. The experimental results are shown in graphs with the construction of corresponding values, tables, equations. General conclusions reported in this article show the finished work confirming the hypothesis of the research and execution of tasks.